Pemberdayaan Kader Usaha Kesehatan Sekolah (UKS) Melalui Pembinaan UKS di SDN I Kalirejo, Kabupaten Banyuwangi - Elita Endah Mawarni (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
SDN I Kalirejo is one of the elementary schools that has many students and it is potential to become a cadre of School Health Unit which is expected to support the sustainability of School Health Unit. This school is no less feasible when compared to other elementary schools in Banyuwangi. From the observations result, the implementation of School Health Unit has not been optimal because of human resources and infrastructure facilities that have not been utilized properly and continuously. To support the continuity and sustainability of School Health Unit program and activities at Kalirejo I Elementary School, guidance and counseling are badly needed in the form of giving skills and health knowledge from competent mentor or counselor, so it is expected to increase the knowledge from the health sectors for local school residents and it will improve their health level automatically.